Inhibitory effect of Fisetin against the aggregation process of SOD1 E100K mutant: computer-based drug design as a potential therapeutic for ALS disease - Seyedi Asl, Fatemeh Sadat; Malverdi, Nasrin; Ataei Kachouei, Fatemeh Sadat; Zarei, Fatemeh; Ghiabi, Shamim; Baziyar, Payam; Nabi-Afjadi, Mohsen (Frontiers in Chemistry, 2025)
Protein misfolding and aggregation in superoxide dismutase 1 (SOD1) are linked to the neurodegenerative disease amyotrophic lateral sclerosis (ALS). SOD1 mutations have a significant role in the pathophysiology and fast behavior of protopathic proteins in ALS illness. The E100K mutation may be useful in uncovering the pathogenic mechanism of SOD1 associated with ALS. According to several studies, giving small molecule inhibitors made from polyphenolic flavonoid compounds may be a viable treatment strategy for neurological conditions. Using molecular docking and MD simulations, we have identified a potential flavonoid drug that may successfully inhibit SOD1’s amyloidogenic activity. Puerarin, Fisetin, and Peonidin provided intriguing pharmacological hints during the initial screening of flavonoids. The Fisetin-E100K complex had a larger residual energy contribution and substantial binding than other flavonoid compounds. The findings showed that, unlike other materials, Fisetin increased the structural stability, hydrophobicity, and flexibility of the mutant while reducing the amount of β-sheets. Furthermore, to distinguish aggregation in the mutant (unbound/bound) states, we displayed modifications in the free energy landscape (FEL). As a result, Fisetin was identified as having therapeutic potential against the E100K, which might make it a viable pharmacological option for the creation of inhibitors that lower the chance of ALS death.